2022
DOI: 10.1590/s1980-657420220006022
|View full text |Cite
|
Sign up to set email alerts
|

Proposals and effects of training using small-sided games for young soccer players: a narrative review

Abstract: This review article aimed to search for studies that used SSG as an intervention in order to verify the effects of physical and tactical performance in young soccer players and to make a critical analysis in the literature of how small games are proposed, how they are controlled and how they affect the performance of soccer players in the short and medium term. Methods: In this narrative review, we searched four databases (PubMed, Scopus, Web of Science, and SPORTDiscus), in total, 242 studies were found. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…There are systematic reviews related to small-sided games. The authors investigated the applications of SSGs in the sports training context with physical, physiological and tactical goals [23][24][25][26]. In the review conducted by [24], nine longitudinal research studies were found, that related to small-sided games, and in five of these, the subjects were junior football players.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are systematic reviews related to small-sided games. The authors investigated the applications of SSGs in the sports training context with physical, physiological and tactical goals [23][24][25][26]. In the review conducted by [24], nine longitudinal research studies were found, that related to small-sided games, and in five of these, the subjects were junior football players.…”
Section: Introductionmentioning
confidence: 99%
“…Oliveira et al [26] performed a critical analysis regarding the way SSGs are applied, how they are monitored and how they influence the performance of football players in the short and medium term. As a conclusion, they found that the use of small-sided games mainly in the form of three vs. three (pitch size between 20 × 25 m and 27 × 36 m) and four vs. four (pitch size between 30 × 35 m and 30 × 40 m) with three and five workouts per week, for at least one month, seems to have beneficial effects in terms of physical performance in junior footballers.…”
Section: Introductionmentioning
confidence: 99%